Lexical innovations are rarely passed on during one's lifetime: Epidemiological perspectives on estimating the basic reproductive ratio of words. - Andreas Baumann (PLoS ONE)
Lexical dynamics, just as epidemiological dynamics, represent spreading phenomena. In both domains, constituents (words, pathogens) are transmitted within populations of individuals. In linguistics, such dynamics have been modeled by drawing on mathematical models originating from epidemiology. The basic reproductive ratio is a quantity that figures centrally in epidemiological research but not so much in linguistics. It is defined as the average number of individuals that acquire a constituent (infectious pathogen) from a single individual carrying it. In this contribution, we examine a set of lexical innovations, i.e., words that have spread recently, in four different languages (English, German, Spanish, and Italian). We use and compare different ways of estimating the basic reproductive ratio in the lexical domain. Our results show that the basic reproductive ratio can be somewhat reliably estimated by exploiting estimates of lexical age of acquisition and prevalence but that the derivation based on diachronic corpus data comes with certain challenges. Based on our empirical results, we argue that the basic reproductive ratio can inform about the stability of newly emerging words and about how often such words are successfully propagated in linguistic contact events. Our analysis shows that an average lexical innovation that has spread in the previous two centuries has been passed on by each individual only to a handful of contacts.